Behavior and design of circular concrete columns strengthened with textile-reinforced mortar subjected to eccentric compression. (May 2023) - Ran, Jinlin; Li, Tingchun; Wang, Hongshan; Zhu, Qingwen; Zhang, Hao; Du, Yiteng; Li, Weiteng
Abstract: Textile-reinforced mortar (TRM) is a cheaper and eco-friendlier material for the concrete confinement than steel and fiber-reinforced polymer (FRP). The behaviors of plain concrete slender columns with circular cross-section strengthened with TRM under eccentric compression were analyzed both experimentally and analytically in this paper. The test results showed that TRM could effectively inhibit the extension of cracks in columns, and increasing the number of textile layers from one to three led to a 44% increase in ultimate load. Meanwhile, the secondary moment of columns relative to the total moment varied from 20% to 35%, which was positively related to the confinement effectiveness of TRM. Then, a comparison of the behaviors of confined concrete columns under axial load-flexural moment (P-M) loading demonstrated that the confinement provided by TRM was relatively insufficient when compared to steel and FRP, behaving a post-peak softening phase of compressive constitutive curves. However, the textile with high tensile strength improved the stress distribution of cross-section of eccentrically loaded columns, thereby observing a much slower reduction in ultimate load with the increase of the eccentric ratio. Finally, according to a cross-section bearing capacity analysis, the procedure of analytical calculations was proposed to predict the ultimate load of TRM-confined concrete columns at a given eccentric ratio. Furthermore, the proposed analytical calculations provided a parametric study to reveal the correlation between the eccentric ratio and the number of textile layers, and then a simplified regression formula for design purpose was developed. This research highlights the behavior and design of concrete strengthened with TRM under P-M loading, which would give researchers and engineers an insight.